Strengthening Agricultural Extension and Advisory Systems : Procedures for Assessing, Transforming, and Evaluating Extension Systems - Swanson, Burton E. (World Bank, Washington, DC, 2016)
The purpose of this paper is to provide information on how to transform and strengthen pluralistic agricultural extension and advisory systems in moving toward the broader goal of increasing farm income and improving rural livelihoods. The focus of this book is primarily on the technical knowledge, management skills, and information services that small-scale farm households will need to improve their livelihoods in the rapidly changing global economy. In addition, the book will also include information on how extension should help all types of farmers in dealing with escalating natural resource problems, including climate change. The primary focus of this paper will be a comparative analysis of different extension strategies, organizational models, institutional innovations, and resource constraints and how an extension system might be transformed and strengthened through specific policy and organizational changes as well as needed investments. This paper is organized into nine chapters. These chapters follow an institution building strategy used by many donors and governments as they seek to improve their extension system. The diagram in Figure one outlines these basic planning, implementation, and evaluation procedures that will be considered. The sections outlined below will provide a brief overview of the different chapters included in this paper.